The Accuracy of Prediction of Birth Weight by Automated Measurement of Fetal Long Bones Using 5D Long Bone versus VOCAL 3D and Conventional 2D Weight Formulae - Borg TF; Hemeda H; Elsherbiny M (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Objectives: To assess the accuracy of 5D automated measurement of long bones, three dimensional VOCAL measurement of fetal thigh volume in prediction of fetal weight in comparison to the conventional two dimensional Hadlock formulas. Methods: This prospective study was conducted at Ain shams university maternity hospital. Forty four pregnant women with singleton pregnancy at 37 to 41 weeks of gestation admitted for planned delivery within 48 hours were enrolled. All patients were examined by 2D, 3D VOCAL and 5D long bones for the purpose of estimating the fetal weight. Each technique was performed by the same examiner for all the patients who were blinded to the results of the two other techniques. Results were compared to actual birth weights using a unified weight scale. The accuracy, precision and agreement between the three types of ultrasound were calculated as well the time needed to perform each technique. Results: The accuracy and precision of 3D measurements were statistically higher than those for 2D measurements (p<0.0001) with poor agreement between these techniques in favor of the 3DVOCAL.On the other hand The accuracy and precision of 5D system was higher than those of 3D with good agreement but the 5D examination is much faster than 3D examination (average 95 seconds versus230 seconds respectively).  Conclusion: Three dimensional ultrasonographic measurement of fetal thigh volume is more accurate than two dimensional Hadlock formula in fetal weight estimation in our population. The new 5D automated long bone represent a faster, more convenient and accurate method for assessment of birth weight.